2004
DOI: 10.1111/j.1365-4632.2004.02072.x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E does not reduce the side‐effects of isotretinoin in the treatment of acne vulgaris

Abstract: Eight hundred IU/day vitamin E did not improve the side-effects of 1 mg/kg/day of isotretinoin in the treatment of acne vulgaris.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 11 publications
0
18
0
2
Order By: Relevance
“…6,10 Supporting previous results, in the current study, major antioxidant enzyme GSH-Px activity, GSH in erythrocytes and LP were analysed in both erythrocytes and plasma as oxidative stress parameters under isotretinoin therapy as well as plasma antioxidant vitamins. Unlike the above studies, Kus et al 35 reported that acne vulgaris patients receiving 1 mgÁkg -1Áday -1 of isotretinoin therapy could not minimize adverse mucocutaneous side effects such as facial erythema, facial dryness, chelitis and serum lipid and liver enzyme profiles by the addition of 800 IUÁday -1 vitamin E in 60 recalcitrant nodular acne patients. Lipid peroxides are the initial products when lipids are damaged by ROS.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…6,10 Supporting previous results, in the current study, major antioxidant enzyme GSH-Px activity, GSH in erythrocytes and LP were analysed in both erythrocytes and plasma as oxidative stress parameters under isotretinoin therapy as well as plasma antioxidant vitamins. Unlike the above studies, Kus et al 35 reported that acne vulgaris patients receiving 1 mgÁkg -1Áday -1 of isotretinoin therapy could not minimize adverse mucocutaneous side effects such as facial erythema, facial dryness, chelitis and serum lipid and liver enzyme profiles by the addition of 800 IUÁday -1 vitamin E in 60 recalcitrant nodular acne patients. Lipid peroxides are the initial products when lipids are damaged by ROS.…”
Section: Discussionmentioning
confidence: 95%
“…In plasma, HDL-cholesterol is the major carrier of lipid peroxides. 35,36 . Hence, plasma LP was found to be lower depending on lower levels of HDL in the treatment group.…”
Section: Discussionmentioning
confidence: 99%
“…There have been various studies investigating potential treatments for isotretinoin-associated cheilitis, including vitamin E supplementation, evening primrose supplementation, and administering lower doses of isotretinoin in an attempt to mitigate side effects. Yet, there are currently no evidence-based effective or preventative treatment options for isotretinoin associated cheilitis [5, 10, 1213]. Therefore there is a significant need for the development of novel treatment options.…”
Section: Discussionmentioning
confidence: 99%
“…Isotretinoin (13-cis retinoic acid) belongs to a group of drugs known as retinoids, which are derivatives of vitamin A. Isotretinoin decreases the size and activity of the sebaceous glands in the skin, thus reducing the amount of sebum produced by the sebaceous glands [1]. Acne vulgaris is common among adolescents and young adults and isotretinoin is frequently administered for this condition.…”
mentioning
confidence: 99%
“…It is the rst-line treatment for extensive and nodulocystic acne [2]. Isotretinoin is also used in moderate acne that is unresponsive to conventional treatment and in patients with obvious scarring [1]. Isotretinoin has adverse e ects on the mucosae, eyes, skin, liver and the musculoskeletal system.…”
mentioning
confidence: 99%